Diffusion and sorption of nitroplasticizers in vinyl copolymer elastomer and its composites. Issue 17 (17th April 2014) - Yang, Dali; Pacheco, Robin; Henderson, Kevin; Hubbard, Kevin; Devlin, David
ABSTRACT To study the aging behavior of cured vinyl copolymer elastomer (VCE) under thermal and nitroplasticizer (NP) environment, we investigated the sorption and diffusion of NP in VCE and its composites. The sorption kinetics of NP into VCE and its composites with respect to filler concentration (0–80%) and temperature (18–70°C) were investigated by conventional gravimetric method. The NP sorption process is endothermic. Kinetic studies show that Fickian diffusion can describe the NP sorption in the VCE polymer. The samples with a high filler concentration show more complicated behavior at low temperature than that at high temperature. The present article discusses the dependences of diffusion coefficient and other related parameters on the polymer concentration and morphological structures of the samples. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40729.